2022
DOI: 10.1021/acsomega.2c00306
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine-type Infrared-820 Encapsulated Polymeric Nanoparticle-Assisted Photothermal Therapy of Cancer

Abstract: Organic small-molecule photosensitizers are well-characterized and known for the light-responsive treatment modality including photodynamic therapy. Compared with ultraviolet–visible (UV–vis) light used in conventional photodynamic therapy with organic photosensitizers, near-infrared (NIR) light from 700 to 900 nm is less absorbed and scattered by biological tissue such as hemoglobin, lipids, and water, and thus, the use of NIR excitation can greatly increase the penetration depth and emission. Additionally, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The key advantages of photo-based therapy include its high specificity, minimal invasiveness and low toxicity. Due to their unique properties, the conjuncted molecules, such as IR-820 55,56 , pyrene 57 , rhein 58 , berberine 59 , camptothecin 60,61 and curcumin 62 , have been formulated into various nano structures 63,64 for exploring their potential in photodynamic therapy (PDT) and photothermal therapy (PTT) for the treatment of various ailments. The formation of Pure Nano systems of the conjuncted molecules provide them with improved nano-structural stability and aqueous dispersity as well as significantly altered photophysical properties, thus further expanding their potential applications in these fields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key advantages of photo-based therapy include its high specificity, minimal invasiveness and low toxicity. Due to their unique properties, the conjuncted molecules, such as IR-820 55,56 , pyrene 57 , rhein 58 , berberine 59 , camptothecin 60,61 and curcumin 62 , have been formulated into various nano structures 63,64 for exploring their potential in photodynamic therapy (PDT) and photothermal therapy (PTT) for the treatment of various ailments. The formation of Pure Nano systems of the conjuncted molecules provide them with improved nano-structural stability and aqueous dispersity as well as significantly altered photophysical properties, thus further expanding their potential applications in these fields.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their unique properties, the conjuncted molecules, such as IR-820 55,56 , pyrene 57 , rhein 58 , berberine 59 , camptothecin 60,61 and curcumin 62 , have been formulated into various nano structures 63,64 for exploring their potential in photodynamic therapy (PDT) and photothermal therapy (PTT) for the treatment of various ailments.…”
Section: More Potential Applicationsmentioning
confidence: 99%
“…Although it can be a quite unexpected result due to the lower hydrophobicity of probes containing R1 and R2 charged groups, such as IR820, this agrees with the ability of the molecules from group 2 to be deeply inserted in the lipid membrane and create membrane defects that ultimately may lead to the disruption of the membrane. Indeed, the data available in the literature point to a higher cytotoxicity of IR820 in MCF-7 cells in the absence of irradiation, i.e., cell viability of 75% for IR820 at 8 µM [ 74 ], while IR780 at 7.5 µM results in a cell viability higher than 80% [ 75 ]. Additionally, in another work, the authors showed a small increase in the BMS202 release without NIR laser irradiation when the IR780 was also loaded on lipid nanoparticles—a total release rate of 56.7% and 51.4% at 72 h in the presence and absence of IR780, respectively [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…PI stains cells can only be identified in necrosis or late apoptosis, while Annexin V can be identified in both the late and early stages of apoptosis. Accordingly, living cells (Annexin V -/PI -, bottom left quadrant), early apoptotic cells (Annexin V + /PI -, bottom right quadrant), late apoptotic cells (Annexin V + /PI + , top right quadrant) and necrotic cells (Annexin V -/PI + , top left quadrant) were classified (Marasini and Aryal, 2022). As observed in Figure 7b, when cells were treated with PO, an increase in the content of both early and late apoptotic cells was observed (30.8% and 18.8%, respectively).…”
Section: Influence Of Po In the Presence Of Pbm On Necrosis Or Apopto...mentioning
confidence: 99%